BATIK KAYU KRÈBÈT YOGYAKARTA : KAJIAN ESTETIKA DAN FUNGSI - Aruman A (Faculty of Humanities, Jember University, 2012)
The development of batik art craft has expanded to diverse materials and techniques. One of them is batik applied to wood media. As applied by the batik art craftmen of Dusun Krebet, Yogyakarta. Wood-based batik art craft has been developed through exploration in traditional batik art that has been hereditarily in existence for generations. In this article, the author seeks to elaborate the structure of batik style formation on wood media and the function of the created product. The discussion is focused on the applied batik style, the patterns of style formation, their functions based on function theories.Keywords: wood batik, aesthetic, function